Pembatasan Tingkat Komponen Dalam Negeri (TKDN) sebagai Hambatan Non-Tarif: Perspektif TRIMs dan Konsekuensi bagi Indonesia - Fergie Brillian Arthaleza (Media Hukum Indonesia (MHI), 2026)
Indonesia uses the Domestic Component Level (TKDN) policy to strengthen the competitiveness of its national industry by increasing the use of local components, but its implementation is closely related to international obligations, particularly within the framework of the Agreement on Trade-Related Investment Measures (TRIMs). This study aims to analyze the regulation and implementation of TKDN in foreign investment and assess its compliance with TRIMs provisions, while identifying potential legal consequences if the policy is deemed inconsistent with WTO commitments. This study uses a normative legal method with a legislative, conceptual, and case approach, supported by primary legal materials in the form of TKDN and TRIMs Agreement regulations as well as secondary legal materials from academic literature. The results of the study show that although TKDN has strategic objectives such as encouraging technology transfer, increasing industrial capacity, and reducing import dependency, some of its provisions have the potential to fulfill the local content requirements prohibited by TRIMs. This condition could lead to the risk of disputes, trade retaliation, and a decline in foreign investor confidence. Therefore, policy harmonization is needed so that TKDN remains effective in supporting national industrial development without conflicting with Indonesia's international trade obligations.